2020
DOI: 10.12973/ijem.6.3.613
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Shared Leadership and Organizational Commitment in Primary and Secondary Schools: Malatya Case

Abstract: Shared leadership enables employees to develop positive feelings for their organizations and themselves. Especially, their devotional feelings and behaviours towards their organizations increase with the sharing of leadership. In this study, the shared leadership of the school and the organizational commitment levels of the teachers, their relationship with each other and the predictive status were examined. This study is a research within relational survey model. The data of the research were collected from 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
(24 reference statements)
0
7
0
3
Order By: Relevance
“…Effective leaders bring everyone together to agree on improvements for continued growth and change (Lyon et al, 2022;Torres et al, 2020). The role of the principal is to discover the talents of their staff, focus on the interactions amongst them (Cobanoglu, 2020;Gronn, 2000), and facilitate an influence on the learning and decisionmaking process throughout the school (Torres et al, 2020). Leithwood et al (2019) emphasized that "school leadership has a significant effect on features of the school organization which positively influences the quality of teaching and learning.…”
Section: Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective leaders bring everyone together to agree on improvements for continued growth and change (Lyon et al, 2022;Torres et al, 2020). The role of the principal is to discover the talents of their staff, focus on the interactions amongst them (Cobanoglu, 2020;Gronn, 2000), and facilitate an influence on the learning and decisionmaking process throughout the school (Torres et al, 2020). Leithwood et al (2019) emphasized that "school leadership has a significant effect on features of the school organization which positively influences the quality of teaching and learning.…”
Section: Leadershipmentioning
confidence: 99%
“…, 2020). The role of the principal is to discover the talents of their staff, focus on the interactions amongst them (Cobanoglu, 2020; Gronn, 2000), and facilitate an influence on the learning and decision-making process throughout the school (Torres et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employees who make decisions together place more value on each other's opinions and thoughts (Gu et al, 2016). Employees who make joint decisions will both influence and support their friends, and increase each other's motivation and responsibility-taking skills (Carson et al, 2007;Cobanoglu, 2020;Pearce et al, 2003). Empowering employees by sharing leadership will ultimately positively influence the organization to achieve its goals.…”
Section: Shared Leadershipmentioning
confidence: 99%
“…In addition, the 21st century teachers are expected have the following characteristics: 1) Experience: being experienced on the new learning method management, 2) Extended: having skills on knowledge acquisition, 3) Expended: having ability to effectively transfer or expand their knowledge to students through technology media, 4) Exploration: having ability to explore and select up-to-date knowledge or contents to be used with students by using appropriate technology and media, 5) Evaluation: being a good and fair assessor who can use technology in evaluation, 6) End-User: being able to use different technology appropriately, 7) Enabler: being able to use technology to create lessons, 8) Engagement: having ability to cooperate and exchange knowledge with each other through technology, develop a network of cooperation such as a community for teachers on the web, 9) Efficient and Effective: being able to use technology effectively as a knowledge producer, knowledge distributor, and knowledge users (Cobanoglu, 2020;Cox, 2019) While Vibulphol ( 2015 ) researched Thai Teacher Education for the Future: Opportunities and Challenges, it was found that teachers play a key role in supporting or suppressing students' learning. Regarding the needs for new kinds of instruction to enhance lifelong learning and skills necessary for the learners' unknown future, educational reform in high performing countries like Finland, Singapore, and South Korea paid close attention to make changes in their teacher education while Thailand has vaguely addressed the issues related to teacher preparation in its recent draft of the educational reform.…”
Section: Introductionmentioning
confidence: 99%